The Use of Cross-Border Corporate Profits and Losses and “Global Corporate Tax Information”: A Game Theory Approach - Garbarino, Carlo (Columbia Journal of Tax Law, 2014)
The paper, proposes a game theory approach based on a concept of Global Corporate Tax Information and analyzes the unilateral strategies a country can select from to regulate cross-border profits and losses in its capacity as a residence-country or as a source-country. A description of the strategies available to residence-countries when there is no exchange of Global Corporate Tax Information is developed in section 2. Section 3 then looks at the interactions of those unilateral strategies of residence and source countries when there is no exchange of Global Corporate Tax Information, and shows that they lead to a stable uncooperative equilibrium as the result of “dominant strategies.” Section 4 emphasizes the strategic importance of Global Corporate Tax Information insofar as it is conducive to effective cooperation in enforcement that prevents aggressive strategies by global taxpayers and shows that such coordination can be backed by multilateral commitment. Section 4 also demonstrates that the Common Consolidated Corporate Tax Base (“CCCTB”) can be viewed as a multilateral method for the exchange of Global Corporate Tax Information if approved by at least nine EU countries (i.e. the minimum number of parties required under the “enhanced cooperation” procedure.) Section 5 concludes by proposing that the U.S. could become a party to pre-existing multilateral systems for exchange of Global Corporate Tax Information such as the CCCTB.